POOR AIR QUALITY IN GOVERNMENT BUILDINGS IS WIDESPREAD (Tufts Archival Research Center, 2007)
American Federation of Government Employees and National Energy Management Institute article on survey regarding poor air quality in government buildings. Finds that many federal employees are suffering from poor air quality and feel their agencies are not responding adequately.